2021
DOI: 10.1002/jor.24987
|View full text |Cite
|
Sign up to set email alerts
|

Infrapatellar fat pad volume and Hoffa‐synovitis after ACL reconstruction: Association with early osteoarthritis features and pain over 5 years

Abstract: Infrapatellar fat pad (IPFP) morphology and Hoffa‐synovitis may be relevant to the development and progression of post‐traumatic osteoarthritis (OA). We aimed to compare IPFP volume and Hoffa‐synovitis in participants with anterior cruciate ligament reconstruction (ACLR) and uninjured controls, and to determine their association with prevalent and worsening early knee OA features and pain in participants post‐ACLR. We assessed IPFP volume and Hoffa‐synovitis from magnetic resonance imaging (MRI) in 111 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Both effusion-synovitis and Hoffa synovitis were shown to be associated with KL grade, joint space width, joint space narrowing, and total subchondral bone marrow lesion volume 33 . Of interest, the prevalence of Hoffa-synovitis prevalence was similar between participants with or without knee injury 34 . After stratification by sex, effusion-synovitis differed between cases and controls in both women and men, whereas Hoffa-synovitis differed only in women.…”
Section: Discussionmentioning
confidence: 91%
“…Both effusion-synovitis and Hoffa synovitis were shown to be associated with KL grade, joint space width, joint space narrowing, and total subchondral bone marrow lesion volume 33 . Of interest, the prevalence of Hoffa-synovitis prevalence was similar between participants with or without knee injury 34 . After stratification by sex, effusion-synovitis differed between cases and controls in both women and men, whereas Hoffa-synovitis differed only in women.…”
Section: Discussionmentioning
confidence: 91%
“…In their study, Hart et al assessed the volume of the Hoffa fat body in patients after anterior cruciate ligament reconstruction and found that the thickening of the Hoffa fat body may be responsible for the early stage of OA of the entire knee. As suggested by the authors, the volume and metabolic activity of IPFP may be an important marker of early OA [ 63 ]. Further studies are required to evaluate IPFP in early OA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hart et al (2022) found that the presence of a larger subpatellar fat pad and Hoffa’s synovitis after ACLR would increase the patient’s odds of having patellofemoral and tibiofemoral cartilage injury at 1 year post-operatively. At 5 years post-operatively, this chance was even seven times as high.…”
Section: Risk Factors Of Cartilage Lesionmentioning
confidence: 99%